Predictors of career indecision among Malaysian undergraduate students - Abu Talib, Mansor; Tan, Kit Aun (Eurojournals, 2009)
Career indecision refers to the phenomenon where individuals especially students are unable to make decisions about the careers they wish to pursue. Career decisions enable us to label students as being either ‘decided’ or ‘undecided’ on their career choices. To a greater extent, career indecision could also invoke the idea of readiness or career maturity in terms of the career developmental tasks they have to complete. The aim of this study was to determine predictive factors of career indecision among Malaysian undergraduates. Data for this study were collected using a self-administered questionnaire. There were 1229 respondents who consisted of undergraduate students from four public universities. The respondents were identified via multistage stratified sampling. The Career Factor Inventory (CFI; Chartrand, Robbins, Morrill & Boggs, 1990) was used to measure career indecision while the My Vocational Situation (MVS; Holland et al., 1980) was used to measure the three core dimensions of career identity namely vocational identity, occupational information and career barriers. The multiple regression analysis indicated that female undergraduates with high academic achievement and low occupational information, and vocational identity were more unlikely to have decided on their career. An understanding of factors contributing to career indecision among university students will provide insights for educators and student personnel in improving the students’ career developmental process.